ADOPSI TEKNOLOGI MUSLIM, SIKAP, DAN INTENSI PEMBELIAN PRODUK INVESTASI ISLAM MENGGUNAKAN FINANCIAL TECHNOLOGY - Maulia Nurul; R. Gratiyana Ningrat (Universitas YARSI, 2019)
The purpose of this research is to examines the muslim’s buying behavior in Islamic Financial Technology products based on their technology adoption. The Structural Equation Model (SEM) proves that there’s significant relationship between Technology Adoption to construct the Buying Attitude. Meanwhile, the Technology Adoption has significant relationship directly to Buying Intention which means the partial mediation of attitude occurs in this model. The Buying Attitude towards Islamic Financial Technology products show significant relationship to buying intention to adopt the Islamic investment products in the future